2018
DOI: 10.1371/journal.ppat.1006953
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of transketolase triggers a stringent metabolic response in promastigotes and loss of virulence in amastigotes of Leishmania mexicana

Abstract: Transketolase (TKT) is part of the non-oxidative branch of the pentose phosphate pathway (PPP). Here we describe the impact of removing this enzyme from the pathogenic protozoan Leishmania mexicana. Whereas the deletion had no obvious effect on cultured promastigote forms of the parasite, the Δtkt cells were not virulent in mice. Δtkt promastigotes were more susceptible to oxidative stress and various leishmanicidal drugs than wild-type, and metabolomics analysis revealed profound changes to metabolism in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…7C). However, as often observed with attenuated Leishmania mutant lines (36)(37)(38), limiting dilution culturing from tissues at the site of injection revealed that some L. major Δdecr parasites persisted 8 weeks post in vivo infection. Thus, DECR is a virulence factor and decr-deficient parasites were unable to cause lesions in a highly susceptible host.…”
Section: Resultsmentioning
confidence: 52%
“…7C). However, as often observed with attenuated Leishmania mutant lines (36)(37)(38), limiting dilution culturing from tissues at the site of injection revealed that some L. major Δdecr parasites persisted 8 weeks post in vivo infection. Thus, DECR is a virulence factor and decr-deficient parasites were unable to cause lesions in a highly susceptible host.…”
Section: Resultsmentioning
confidence: 52%
“…For LC-MS metabolomic analyses, sample extraction was performed as described (Creek et al, 2011; Kovářová et al, 2018). In summary, 10 8 cells were rapidly cooled in a dry ice/ethanol bath to 4 °C, centrifuged, washed with 1 × PBS, and resuspended in 200 μL extraction solvent (chloroform:methanol:water, 1:3:1 vol ratio).…”
Section: Methodsmentioning
confidence: 99%
“…While the abundance of carbon sources such as sucrose and 3 hexose-multimers (labelled as cellopentaose, cellohexaose and celloheptaose) were identified as increasing in quiescent cells. These penta, hexa and heptahexoses have previously been inferred [31] to derive from mannogen, a poly-mannose carbohydrate reserve used by Leishmania [32]. Interestingly, while most structural phospholipids were not modulated, a number of free fatty acyls and also sphingolipids were increased in quiescent promastigotes, while no clear trend was observed in amastigotes.…”
Section: Metabolomicsmentioning
confidence: 86%